An Insight Into the Mechanism of Plant Organelle Genome Maintenance and Implications of Organelle Genome in Crop Improvement: An Update - Mahapatra, Kalyan; Banerjee, Samrat; De, Sayanti; Mitra, Mehali; Roy, Pinaki; Roy, Sujit (Frontiers in Cell and Developmental Biology, 2021)
Besides nuclear genome, plants possess two small extra chromosomal genomes in mitochondria and chloroplast, respectively, which contribute a small fraction of the organelles’ proteome. Both mitochondrial and chloroplast DNA have originated endosymbiotically and most of their prokaryotic genes were either lost or transferred to the nuclear genome through endosymbiotic gene transfer during the course of evolution. Due to their immobile nature, plant nuclear and organellar genomes face continuous threat from diverse exogenous agents as well as some reactive by-products or intermediates released from various endogenous metabolic pathways. These factors eventually affect the overall plant growth and development and finally productivity. Detailed mechanism of DNA damage response and repair following accumulation of various forms of DNA lesions, including single and double-strand breaks have been well documented for nuclear genome and now it has been extended to the organelles. Recent studies have shown that both mitochondria and chloroplast possess a counterpart of most of the nuclear DNA damage repair pathways and share remarkable similarities with different damage repair proteins present in nucleus. Among various repair pathways, homologous recombination is crucial for repair and evolution of organelle genomes. Along with repair pathways, various other factors, including the MSH1 and WHIRLY family proteins, WHY1, WHY2, and WHY3 are also known to be involved in maintaining low mutation rates and structural integrity of mitochondrial and chloroplast genome. SOG1, the central regulator in DNA damage response in plants, has also been found to mediate endoreduplication and cell-cycle progression through chloroplast to nucleus retrograde signaling in response to chloroplast genome instability. Various proteins associated with the maintenance of genome stability are targeted to both nuclear and organellar compartments, establishing communication between organelles as well as organelles and nucleus. Therefore, understanding the mechanism of DNA damage repair and inter compartmental crosstalk mechanism in various sub-cellular organelles following induction of DNA damage and identification of key components of such signaling cascades may eventually be translated into strategies for crop improvement under abiotic and genotoxic stress conditions. This review mainly highlights the current understanding as well as the importance of different aspects of organelle genome maintenance mechanisms in higher plants.